The training of physical education teachers in Portugal, the USA, and Brazil from the perspective of professionalization of teaching during the practicum - Ananias, Elisangela Venancio; de Souza Neto, Samuel; Benites, Larissa Cerignoni (Education Policy Analysis Archives, 2022)
This research, with a qualitative approach of the multiple case study type, aimed to identify and analyze the influence of the movement for the professionalization of teaching (MPT) in three contexts of physical education teacher training practicum proposals. As a result, it was pointed out that in Portugal, the Bologna process represented the guiding principle of an integrated proposal for the European context for training and practicum; in the USA, the parameters prescribed in the manuals consolidated a proposal for teacher training and reorganized the practicum; and, in Brazil, the law of guidelines and bases for national education established principles for thinking about teaching as a profession and area of knowledge, promoting new interpretations for practicum. In conclusion, the MPT influenced training and the practicum in all contexts, but with different perspectives.